An overview of the present and future uses of the CSU IRIS/DRSES - Laybe, Pat, author (Colorado State University. Libraries, 1983)
The purpose of this report is to inform potential scientific users of the capabilities of the CSU IRIS/DRESES. This report is intended to be a descriptive reference which is organized into three chapters. The first chapter presents the facilities which comprise the IRIS/DRSES. The next chapter describes the specific routines necessary to produce research oriented meteorological products presently operational at this time. Current plans for future additions to IRIS/DRSES are described in the last chapter.
July 1983.
Keywords: Satellite meteorology -- Colorado; Imaging systems in meteorology